Multi‐species hotspots detection using self‐organizing maps: Simulation and application to purse seine tuna fisheries management. Issue 12 (17th October 2022) - Stephan, Pauline; Gaertner, Daniel; Perez, Ilan; Guéry, Loreleï
Abstract: To fulfil fisheries management objectives that often include implementing the precautionary and ecosystem‐based approaches, multispecies fisheries data need to be analysed. Amongst the different methods dealing with these multidimensional data, self‐organizing maps (SOMs) remain rarely used, although they are highly flexible in data input and offer visualization possibilities particularly suited to summarize complex datasets. Here, we propose to combine SOMs with a clustering approach to break down data complexity and produce simple geographic maps showing catch hotspots, which can indicate sensitive zones in terms of fishery management. To promote this approach, we tested it first on simulated datasets and then on the open‐access ICCAT commercial catch database of the tropical tuna fisheries of the Atlantic Ocean. We aimed to detect drifting fish aggregating devices (dFADs) catch hotspots of juveniles of two tuna species, bigeye and yellowfin tunas and of the silky shark, a commonly bycaught vulnerable shark species, in tropical tuna purse seine fisheries. Simulations on datasets increasing in complexity (in number, geographic and duration extent of the hotspots and number of species in the analysis) informed us about the method's sensitivity and limits. Our findings showed that, in the context of multi‐specific fisheries, the detection of the hotspot is dependent on a certain level of catch within the hotspot and that adding species to the analysis tended to mask small and short‐duration hotspots. Applied to tropical tuna fisheries' data, the method confirmed the empirical knowledge on which first time‐area closures were based and provided scientifical support. All in all, the visual support provided by the method, its interpretability and its potential transferability to other fisheries' systems constitute its main strengths and imply a possible implementation in management decisions; specifically, as a tool to reach agreement between stakeholders in the definition of regulated areas for protecting juveniles of tunas and vulnerable associated species to dFAD practices. Résumé: Pour atteindre les objectifs de gestion des pêches, qui incluent souvent l'application des approches de précaution et écosystémique, des données multi‐spécifiques ont besoin d'être analysées. Parmi les différentes méthodes permettant de traiter ces données multi‐dimensionnelles, les cartes de Kohonen ('self‐organizing maps' ou SOM) restent rarement utilisées malgré leur flexibilité quant aux données d'entrées et leurs possibilités de visualisation. Nous proposons ici de combiner les SOM à une méthode de clustérisation afin de décomposer la complexité des données et de produire de simples cartes géographiques indiquant les zones de fortes prises multi‐spécifiques, zones sensibles en matière de gestion. Afin de défendre cette approche, nous l'avons d'abord testée sur des données simulées puis sur les données commerciales des pêcheries thonières de l'Atlantique tropical, libres d'accès sur le site de la CICTA. Notre objectif était de détecter les zones de fortes prises de juvéniles de thon obèse et de thon albacore, ainsi que du requin soyeux, prise accessoire fréquente des thoniers senneurs de cette zone. Des simulations de données de plus en plus complexes (en nombre, durée et extension géographique des zones de forte abondance) nous ont permis d'évaluer la sensibilité et les limites de la méthode. Nos résultats montrent que, dans un contexte de pêche multi‐spécifique, la détection des zones de fortes prises dépend d'un certain tonnage. Elle dépend également du nombre d'espèces présentes dans l'analyse. Appliquée au jeu de données des pêcheries thonières tropicales, la méthode a confirmé le savoir empirique sur lequel se basait les premières zones moratoires. En somme, le support visuel généré par la méthode, son interprétabilité et sa transférabilité à d'autres systèmes de pêche constituent sa force et supposent une possible utilisation en support de décision. Ce pourrait être notamment utile pour parvenir à un accord entre acteurs pour définir des zones moratoires de protection des juvéniles de thons et d'espèces associées sensibles.